Bora Laskin : bringing law to life - Girard, Philip (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2005)
In Bora Laskin, Girard chronicles the life of a man who, at all points of his life, was a fighter for a better Canada: he fought antisemitism, corporate capital, omnipotent university boards, the Law Society of Upper Canada, and his own judicial colleagues in an effort to modernize institutions and re-shape Canadian law.
Keywords: Laskin, Bora.; Canada. -- Supreme Court -- Biography.; Canada. -- Cour suprême -- Biographies.; Laskin, Bora; Canada. -- Supreme Court; Judges -- Canada -- Biography.; Juges -- Canada -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges.; LAW -- Civil Procedure.; LAW -- Legal Services.; POLITICAL SCIENCE -- Government -- Judicial Branch.; LAW -- Legal History.; Judges; Canada; Electronic books.; Biographies